Correlation of Enzyme Inhibitor Activity in Sengon with Boktor Larval Growth on Artificial Diet - Ulfah Juniarti Siregar; Noor Farikhah Haneda; Laura Flowrensia (Jurnal Silvikultur Tropika, 2011)
Sengon  (Paraserianthes falcataria  (L) Nielsen) is widely planted for reforestation programs, especially in establishment of community forest as its timber is utilized for constrction, package box, lighter as well as raw material of pulp and paper. However, there is main problem in sengon plantation, which is boktor (Xystrocera festiva Pascoe) pest attact. In the midgut of boktor larvae it was detected trypsin and α-amylase enzymes activity. Whereas on sengon tree it was reported contains inhibitory substance against trypsin and α-amylase enzymes of boktor larvae. The inhibitory activity was assumed as defense mechanism of sengon tree against the pest attack. In order to clarify the assumption an investigation on the correlation between trypsin and α-amylase inhibitor of sengon with larval growth on an artificial diet is necessary. The experiments aimed at obtaining correlations between the activities of trypsin and α-amylase inhibitors of sengon tree with the growth of boktor larvae, with small (±1,5 cm) and big sizes (±3 cm) on an artificial diet containing respective sengon tree materials.